The burden of mental disorders in the Eastern Mediterranean region, 1990-2015: findings from the global burden of disease 2015 study - Charara, Raghid; Bärnighausen, Till; Jonas, Jost B. (International journal of public health, 2017)
Mental disorders are among the leading causes of nonfatal burden of disease globally.
Gesehen am 23.04.2020